Irish Unification After Brexit: Old and New Political Identities?. Issue 1 (17th October 2022) - Diamond, Patrick; Colfer, Barry
Abstract: This article contends that the outcome of the prolonged dispute about the future constitutional status of Northern Ireland (NI) will be shaped by the emerging dynamic between 'old' and 'new' political identities in NI. The 'old' identities conceived political outcomes as defined by two monolithic ethno‐cultural blocs: nationalism (alongside republicanism) and unionism (alongside loyalism). Nationalism and unionism formed the 'two communities model' of consociational governance enshrined in the Belfast/Good Friday Agreement (B/GFA). Today, despite the Agreement being in existence for over twenty years, growing numbers of citizens identify with neither ethno‐cultural category. Recent elections indicate that more pluralistic 'new' political identities are gaining ground at the expense of traditional alignments. The implications for NI's constitutional future are likely to be profound. The emerging constituency of non‐aligned voters will have a decisive impact on the final outcome of any border poll on Irish unification. Such voters typically support the cross‐community Alliance Party, the Greens, or the left People Before Profit (PBP) party. Crucially, these parties are concerned as much with economic and social issues as constitutional questions. In the context of growing political fluidity, the result of any future border poll remains contingent.